Hemogram components and platelets count variation in anemic patients attending Birat Medical College and Teaching Hospital, Morang, Nepal (Journal of Pathology of Nepal, 2021)
Background: Anemia being the expression of the underlying disease is a global public health problemaffecting both developing as well as developed countries. The RBC indices and platelet count variationamong anemic patients are important to know their association for clinical implications.Materials and Methods: A hospital-based cross-sectional study among anemic patients with hemoglobin